Community responses of arbuscular mycorrhiza fungi to hydrological gradients in a riparian Phragmites australis wetland - Xue‐dong Chen; Ying Zhu; Mei‐na Feng; Ji‐hang Li; Ming‐yan Shi (Ecology and Evolution, 2024)
Abstract The hydrological regime is considered to be the major factor that affects the distribution of arbuscular mycorrhiza (AM) fungi in wetlands. We aimed to investigate the responses of AM fungal community to different hydrological gradients. Illumina Miseq sequencing technology was used to study the AM fungal community structure in roots and rhizosphere soils of Phragmites australis in different moisture areas (dry area, alternating wet and dry area, and flooded area) in Mengjin Yellow River wetland. The rhizosphere soils and roots hosted different AM fungal communities. In roots, the AM fungal colonization and Chao1 richness in dry area were significantly higher than that in alternating wet and dry area and flooded area, but the community composition did not vary clearly under different water conditions. In rhizosphere soils, the Chao1 richness of AM fungi in flooded area was significantly higher than that in alternating wet and dry area and dry area, and the AM fungal community structure obviously differed across different areas. The redundancy analyses indicated that changes in the AM fungal community in soils were associated with altered soil properties, and the abundance of the dominant genus Glomus was mostly positively correlated with alkali‐hydrolyzable nitrogen in soils. This study helps us to understand the responses of AM fungal community to hydrological gradients in wetlands.